Study Of Association of Psychological Stress and Depression Among Undergraduate Medical Students in Pondicherry - Kittu, Devi; Patil, Rohan (National Journal of Community Medicine, 2013)
Background: Medical education across the globe is perceived as being inherently stressful. Studies on psychological problems such as stress, depression and anxiety among medical students have found that these disorders are under diagnosed and under treated. In this background the present study was undertaken with the objectives to assess the magnitude of depression and its association with stress among medical students. Methods: A Cross sectional study was undertaken among 235 medical students in a private medical college, Pondicherry. Tools similar to General Health Questionaire (GHQ-12) and Beck depression Inventory (BDI) was used to screen psychological stress and depression respectively. Results: The prevalence of depression was 71% among medical students. Psychological stress was associated with depression. Conclusion: Emphasize should be laid on the importance of screening for depression of medical students on a regular basis for early detection and rendering appropriate intervention like group counseling, stress management training etc. to protect the future professionals.